JRE4 is a master transcriptional regulator of defense‐related steroidal glycoalkaloids in tomato. (29th April 2018) - Nakayasu, Masaru; Shioya, Naoki; Shikata, Masahito; Thagun, Chonprakun; Abdelkareem, Ayman; Okabe, Yoshihiro; Ariizumi, Tohru; Arimura, Gen‐ichiro; Mizutani, Masaharu; Ezura, Hiroshi; Hashimoto, Takashi; Shoji, Tsubasa
Summary: Steroidal glycoalkaloids (SGAs) are specialized anti‐nutritional metabolites that accumulate in Solanum lycopersicum (tomato) and Solanum tuberosum (potato). A series of SGA biosynthetic genes is known to be upregulated in Solanaceae species by jasmonate‐responsive Ethylene Response Factor transcription factors, including JRE4 (otherwise known as GAME9), but the exact regulatory significance in planta of each factor has remained unaddressed. Here, via TILLING‐based screening of an EMS‐mutagenized tomato population, we isolated a JRE4 loss‐of‐function line that carries an amino acid residue missense change in a region of the protein important for DNA binding. In this jre4 mutant, we observed downregulated expression of SGA biosynthetic genes and decreased SGA accumulation. Moreover, JRE4 overexpression stimulated SGA production. Further characterization of jre4 plants revealed their increased susceptibility to the generalist herbivore Spodoptera litura larvae. This susceptibility illustrates that herbivory resistance is dependent on JRE4 ‐mediated defense responses, which include SGA accumulation. Ethylene treatment attenuated the jasmonate‐mediated JRE4 expression induction and downstream SGA biosynthesis in tomato leaves and hairy roots. Overall, this study indicated that JRE4 functions as a primary master regulator of SGA biosynthesis, and thereby contributes toward plant defense against chewing insects. Significance Statement: Based on analysis of a mutant of JRE4 with impaired DNA‐binding activity, we show that this ERF transcription factor functions in tomato as a primary master regulator of SGA biosynthesis and contributes towards plant defense against chewing insects.